Heidegger’s Philosophical Anthropology and its Application to the Police in the UK: A Realistic Reflection - Adlam, Robert (Philosophy and Realistic Reflection, 2025)
This paper is written from an ‘insider’ and decades-long practitioner-based set of experiences whilst the author was working as an academic director of studies at the UK Police College, Bramshill. It begins by briefly identifying and characterising the College as a particularly distinct cultural institution. It underlines the fact that the academic staff found themselves constantly coping with the challenging realities presented to them during their encounters with experienced police oﬃcers attending residential courses of management and leadership development at the College. The idea of people as ‘coping’ beings constitutes a central and fundamental aspect of Martin Heidegger’s philosophy; consequently, in a relatively substantial section, and aided by several scholarly analyses, the paper moves on to provide a detailed outline of some key features of his philosophy; this includes an ongoing ‘realistic reflection’ on how Heidegger’s celebrated ‘philosophical anthropology’ and his analysis of the ‘technological understanding of being’ serve as a way of illuminating and theorising the conduct of the police at the Police College, their wider situations of practice - and the overall ‘being’ of people in general. Heidegger’s suggestion about how to resist the alienating effects of the quest for effciency through the ‘saving power of insignificant things’ is noted - and which links Heidegger’s thinking with aspects of non-western philosophy and culture, including ‘Wabi Sabi’, and certain holistic works of anthropology. The paper concludes by providing a brief answer to the question, ‘Does a Heideggerian analysis of police culture suggest ways in which that culture could be improved?’